The Effect of Game Playing and Goal Orientation on Creativity - Mun, Jungim (Frontiers in Psychology, 2022)
In an effort to bolster employee creativity, companies like Google and Groupon have adopted indoor work-spaces that incorporate slides, swings, and unconventional design. While it may be costly and time-consuming to change certain aspects of a firm's work environment (e.g., the room design) to aid creativity and brainstorming, it is relatively easy for managers to encourage employees to engage in certain forms of unstructured recreation immediately prior to creative-based tasks for a new product development. This research addresses an important oversight in the literature by exploring the effect of cognitive game playing and goal orientation on subsequent new product development creativity. It was found that a cognitive game that engenders a greater degree of fun results in greater creativity on a subsequent new product development task, compared to both a cognitive-based game that engenders less fun and to a control group. Furthermore, it was found that, for a cognitive-based game that engenders a high degree of fun, individuals who are primed with a process goal orientation are more likely to be creative on a subsequent new product development task than those who are primed with an outcome goal orientation.